The making of TVET systems in middle-income countries: insights on Brazil and Chile? - Rambla, Xavier [Verfasser]; Castioni, Remi [Verfasser]; Sepulveda, Leandro [Verfasser] (My University, 2020)
"Although the challenges of Technical and Vocational Education and Training (TVET) have become apparent in middle-income countries, the making of these systems has not been systematically theorised and compared. This article discusses such processes in Brazil - recognised emerging economy, and Chile - one of the last economies to join the high income group. The former has built a standardised TVET system dominated by both the state and companies. In the latter, the standardisation of TVET is low and neither the state nor companies are very active. Drawing on international and the national literatures, the article points at two important factors that have significantly shaped TVET systems in these countries. Firstly, the international agenda has contributed to expanding these systems within the wider framework of lifelong learning policies. Secondly, endogenous sequences of political change and institutional consolidation have configured particular arrangements in each country. Currently, Brazil and Chile face major challenges in integrating sub-sectors of TVET and overcoming inequalities." (authors' abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.3.3 Lateinamerika; Berufsbildungssystem; Internationaler Vergleich; Chile; Brasilien